Topical Breast Milk as an Alternative Prevention Intervention of Omphalitis in Newborn: Case Study - Ernawati, Ernawati (Nursing Case Insight Journal, 2024)
Two newborns were analyzed for the fall of the umbilical cord. One of the babies received intervention with topical breastmilk 3 times a day until pupation, while baby B was given dry method intervention. The data collection technique was interviews and observation. The process of releasing the umbilical cord in babies with topical breast milk until the 4th day without odor appearing. In baby B, the detention occurred on the 7th day by leaving a smelly and wet at the base of the umbilical cord. The Topical Breastmilk method was effective and faster in pulling the umbilical cord than the dry method. So that, it can be used as a recommendation in umbilical cord care.